Preventive Home Visit Strategy in Guidance and Counseling Services to Reduce Delinquency in At-Risk Students - Benyamin Ngongu Kabata; Meggi Dina Mariana Labkoli; Sefrianus Naiheli (Civiliza Publishing, Indonesia., 2026)
At-risk student delinquency is a problem in education that can disrupt the learning process, reduce discipline, and negatively impact the social atmosphere at school. This study aims to examine the Home Visit strategy as part of guidance and counseling services to reduce at-risk student delinquency at Nesi Neonmat Private High School in Kupang City. This research method uses a descriptive qualitative approach. The study subjects included guidance and counseling teachers and students considered at-risk. Data collection techniques used interviews, questionnaires, and a review of school documents. Data analysis was conducted inductively, with stages such as data reduction, data presentation, and drawing conclusions. The results indicate that the Home Visit strategy was implemented effectively and contributed to reducing student delinquency, particularly in cases of truancy, tardiness, and minor disciplinary violations. Furthermore, this strategy strengthens collaboration between the school and parents in fostering sustainable positive student behavior.